La ciudad escenográfica: centro y margen en Buenos Aires - Agnese Codebò (Les Cahiers ALHIM)
By analyzing the texts of Enrique Gómez Carrillo and Jules Huret (travelers who visited Argentina during the celebrations of the Centenary of Independence), the hygienist chronicles of Gabriela Laperrière de Coni, as well as the most recent studies of James Scobie and Jorge Liernur, this article proposes an understanding of Buenos Aires at the turn of the twentieth century as a scenographic city. It was as such that the city would manifest itself in its reading as a continuous entity promoted by the oligarchic elite during the urban modernization, which, on the one hand, produced the elegant Avenida de Mayo, and on the other, the aporias of urban poverty symbolized by the Barrio de las Ranas. These attempts to promote a homogeneous and disciplined vision of the city collided, however, with the urban space understood as a perennially contested and plurally-constituted territory.